COARSE FACE, HYPOTONIA, AND NEURODEVELOPMENTAL REGRESSION - Miranda, A (2020)
Inborn errors of metabolism are a heterogeneous class of multisystemic diseases which, although individually rare, are collectively quite common. Central nervous system is usually affected. The authors report the case of a five-month-old girl, daughter of non-consanguineous parents, born after an unremarkable full-term pregnancy and delivery. Hypotonia and neurodevelopmental regression were noted from the age of five months, along with progressive onset of facial dysmorphism, hepatomegaly, seizures, and dilated cardiomyopathy. Gangliosidosis type 1 diagnosis was confirmed by biochemical, enzymatic, and genetic findings. This report enhances the relevance of multidisciplinary approach and follow-up.